2022
DOI: 10.1183/23120541.00061-2022
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography on lung cancer screening is useful for adjuvant comorbidity diagnosis in developing countries

Abstract: PurposeTo analyze and quantify the prevalence of six comorbidities from lung cancer screening (LCS) on computed tomography (CT) scans of patients from developing countries.MethodsFor this retrospective study, low-dose CT scans (n=775) from patients who underwent LCS in a tertiary hospital between 2016 and 2020 were examined. Age and sex- matched control group was obtained for comparison (n=370). Using the software, coronary artery calcification (CAC), the skeletal muscle area (SMA), interstitial lung abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…The fabricated fibroglandular, pectoral muscle, and skin tissue revealed mean CT and SD HU values of 60.033±4.414, 62.367±10.334, and 132.493±4.45 HU, respectively. These values are found to be consistent with [ 12 , 25 , 26 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The fabricated fibroglandular, pectoral muscle, and skin tissue revealed mean CT and SD HU values of 60.033±4.414, 62.367±10.334, and 132.493±4.45 HU, respectively. These values are found to be consistent with [ 12 , 25 , 26 ].…”
Section: Resultssupporting
confidence: 84%
“…In this work, we developed a patient-based heterogeneous breast phantom that mimicked skin, adipose, fibroglandular, muscle tissue, and carcinoma in the breast while screened with −29 to 150 [26] Skin 132.493 100.75 [12] ±4.45 ±28.9 [12] https://doi.org/10.1371/journal.pone.0284531.t005…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bone density affects implant failures and complications as well (21). According to a study on iatrogenic rib fractures and the risks of death associated with them, complications from treatment-particularly cardiopulmonary resuscitation-are to blame for 80.1% of iatrogenic rib fractures (22). Additionally, during pulmonary resections, accidental rib fractures, which can happen in thoracotomy, are frequently linked to higher postoperative morbidity (6).…”
Section: Discussionmentioning
confidence: 99%